New type of alginate/chitosan microparticle membranes for highly efficient pervaporative dehydration of ethanol. Issue 69 (27th November 2018) - Dudek, Gabriela; Turczyn, Roman
Abstract : A new type of composite alginate membranes filled with CS and three different modified chitosan submicron particles, i.e. CS-P, CS-G and CS-GA were prepared, and the pervaporation of water/ethanol mixture was investigated. Abstract : A new type of composite alginate membranes filled with chitosan (CS) and three different modified chitosan submicron particles, i.e. phosphorylated (CS-P), glycidol (CS-G) or glutaraldehyde (CS-GA) crosslinked ones, were prepared, and the pervaporation of water/ethanol mixture was investigated. The influence of various chitosan particles and their content on the transport properties of membranes was discussed. It was found that the addition of chitosan particles into the alginate matrix has a prominent effect on the ethanol/water separation efficiency. All tested membranes are characterized simultaneously by a high flux and selectivity, exhibiting advantageous properties, and outperforming numerous conventional materials. The best results were achieved for alginate membranes filled with phosphorylated chitosan particles at 10 wt%, for which separation factor, flux and PSI were equal to 136.2, 1.90 kg m −2 h −1 and 256.9 kg m −2 h −1, respectively.